PENGARUH KOMPENSASI TAMBAHAN PENGHASILAN PEGAWAI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN TANJUNG JABUNG TIMUR - Zulfandi; Kiki Helencia (JUMANJI (JURNAL MANAJEMEN JAMBI), 2019)
The purpose of this study is to determine the picture and describe the additional compensation of employee income, organizational culture, job satisfaction and employee performance, know and analyze the effect directly and indirectly of additional compensation of employee income and organizational culture on job satisfaction in the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Tanjung Jabung Timur. The results of this study state that compensation for additional employee income and organizational culture through job satisfaction simultaneously has a positive effect on employee performance. there was a simultaneous direct influence of 19.56% and a simultaneous indirect influence of 2.67% so that the total simultaneous influence was 22.23%, from compensation for additional employee income and organizational culture through job satisfaction on employee performance in the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Tanjung Jabung Timur. Additional compensation of employee income and organizational culture and through job satisfaction partially positively affects employee performance additional compensation of employee income and organizational culture through job satisfaction partially affects employee performance, direct effect X 1 of 9.28% and indirect influence of 2.67%, so the total effect of additional compensation of employee income on performance through job satisfaction is 11.95% and the effect of direct X 2 of 10.28% and indirect influence of 2.09% and the total influence of organizational culture variables on employee performance in Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Tanjung Jabung Timur is 12.37%.